Erich Fromm's Psychoanalytic Theory: Psychology of Character in Mu'tamar Al-Hub's short story "In a Love Banquet" by Taufiq Al-Hakim - Fika Putri Mei Sandy; Darisy Syafa'ah; Latif Amrullah (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2022)
The short story entitled Mu'tamar Al-Hub by Taufiq Al-Hakim is a short story that contains the theme of love. The short story is interesting because it contains different views on the understanding of love. This study examines the psychology of the character in the short story which focuses on the characteristics of each character's love. The method used in this study is a qualitative method with the psychoanalytic theory of Erich Fromm. In this study, researchers found two divisions of the psychology of love in the short story character Mu'tamar Al-Hub. That is, found four forms of essential elements of love and five forms of objects of love. First, the researcher found the psychology of journalist characters who showed an attitude of concern, and responsibility and included in the type of erotic love. Second, the psychology of the musician character shows responsibility and the type of love in the form of motherly love. Third, the psychology of the poet’s character shows the respect and love included in the category of brotherly love and erotic love. Fourth, the psychology of the female character shows that there are aspects of her knowledge and love character in the form of self-love